Optimal non‐invasive diagnosis of fetal achondroplasia combining ultrasonography with circulating cell‐free fetal DNA analysis. (28th November 2018) - Vivanti, A. J.; Costa, J.‐M.; Rosefort, A.; Kleinfinger, P.; Lohmann, L.; Cordier, A.‐G.; Benachi, A.
ABSTRACT: Objectives: To assess the performance of non‐invasive prenatal testing (NIPT) for achondroplasia using high‐resolution melting (HRM) analysis, and to propose an optimal diagnostic strategy combining ultrasound examination and cell‐free fetal DNA (cffDNA) analysis. Methods: In this prospective multicenter study, cffDNA was extracted from blood of pregnant women at risk for fetal achondroplasia (owing to paternal achondroplasia, previous affected child or suspected rhizomelic shortening) and of pregnant low‐risk controls. The presence of either one of the two main fibroblast growth factor receptor 3 gene ( FGFR3 ) mutations was determined using HRM combined with confirmation by SNaPshot minisequencing. Results were compared with phenotypes obtained using three‐dimensional computed tomography or postnatal examination, and/or molecular diagnosis by an invasive procedure. Fetal biometry (head circumference and femur length) was analyzed in order to develop a strategy in which cffDNA analysis for diagnosis of achondroplasia is offered only in selected cases. Results: Eighty‐six blood samples from women at risk for fetal achondroplasia and 65 from controls were collected. The overall sensitivity and specificity of NIPT were 1.00 (95% CI, 0.87–1.00) and 1.00 (95% CI, 0.96–1.00), respectively. Critical reduction in femur length of affected fetuses could be observed from 26 weeks' gestation. Conclusions: HRM combined with SNaPshot minisequencing is a reliable method for NIPT for achondroplasia. Its implementation in routine clinical care combined with ultrasonography is an efficient strategy for the non‐invasive diagnosis of achondroplasia. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.